The correlation between histologic placentitis and amnionitis and the amnioniotic fluid's inflammatory cytokines in case of spontaneous pre-term labor with intact membrane (Medical Journal of Indonesia, 2001)
Pre-term labor is presumed to result from spreading of lower genital infection to upper part, subsequently to decidual and choioamniotic tissues. Host response to this injury include the expression of protein which is responsible to the inflammatory reactions. The expression of the inflammatory cytokines such as IL-β, IL-6, IL-8 and TNF-α increase in case of infection. These cytokines may play an essential role in the pathophysiology of spontaneous pretem labor with intact membrane. An observational analytic cohort study was caried out on cases of spontaneous pre-term labor with intact membrane. The objectives of this study are to examine the relationship between 1) the histologic amnionitis and placentitis and the incidence of preterm delivery,2) the expression of amniotic fluid's IL-β, IL-6, IL-8 and TNF-α and the incidence of preterm delivery, 3) the level of amniotic fluid's IL-β, IL-6, IL-8 and TNF-α and the grade of histologic amnionitis and placentitis in case of pre-term labor with intact membrane. Cases of spontaneous pre-term labor with intact membrane which underwent transabdominal amniocentesis at admission and managed as standard procedure for pre-term labor with intact membrane. All of the cases were observed until the delivery of the baby, eithir preterm or term. The membrane and the placenta were cut postnatally and then the histologic acute inflammation eyaluated based on the criteria of Salafia.The level of amniotic fluid IL-β, IL-6, IL-8 and TNF-α were analyzed quantitatively by Elisa method. This study showed that the degree of histologic amnionitis and placentitis, and the level of amniotic fluid's IL-β, IL-6, IL-8 and TNF-α were significantly higher in pre-term compared to terrn deliveries (p<0.05) and there were a positive correlation between the grade of histologic inflammation and the level of amniotic fluid's cytokines (Spearmann Rank Correlation test; p<0,05) in cases of preterm labor with intact membrane. The higher the grade of histologic amnionitis and placentitis, the higher the level of arnniotic fluid's IL-β, IL-6, IL-8 and TNF-α resulting in a higher risk of pre-term delivery in case of prererm labor with intact membrane. These correlation moy indicate a progression of inflammation from placenta and membrane into the amniotic cavity. (Med J Indones 2001; 10: 203-9) Keywords: Inflammation, Preterm Labour